Advances in global leadership. Vol. 8 - Osland, Joyce; Li, Ming; Wang, Ying (Advances in global leadership,, 2014)
Volume 8 of Advances in global leadership includes timely and impactful chapters on various concepts and processes associated with leading across cultures and other boundaries. Amidst accelerating complexity and global inter-connectedness, a deeper understanding of the variables associated with international leadership is ever more important.